Review of M. Shinohara. (1986). Ideological critiques of the mainstream special education discourse on "protecting the educational rights of children with disabilities": Focusing on human reciprocity, or ensuring development? ["Syogaiji-no-kyoiku-ken" shiso-hihan: Kankei-no-sozo-ka hattatu-no-hosyo-ka] - Suzuki, Maho (Disability Studies Quarterly, 2008)
No abstract available